Improving Students' Critical Thinking and Writing Skills: Implementation using Integrated Problem Based Learning JEMBER Model Development - Ekawati, Wahyu; ., Mustaji; Jannah, Miftakhul (Journal of Posthumanism, 2025)
This study aims to examine the impact of implementing the JEMBER-IPBL model on improving students' critical thinking and writing skills, especially in English learning in vocational high schools. This study used a quasi-experimental design. The subjects of this research were 60 students from two classes of the Agribusiness Food Crops and Horticulture program in grade XI at vocational high school 5 Jember, during the 2024/2025 academic year. The sample was selected through purposive sampling. The aim of this study was to assess the effectiveness of the JEMBER Integrated Problem-Based Learning (IPBL) model in enhancing students' critical thinking and writing skills. The experimental group achieved an average score of 83.20, while the control group averaged 72.90. The corresponding p-value was 0.03, which is less than 0.05. the post-test outcomes demonstrated a notable increase, with the experimental group scoring an average of 83.67 compared to 76.17 in the control group. The p-value for this comparison was 0.038, which is less than 0.05. Therefore, this study indicates that the IPBL JEMBER model is effective in boosting both critical thinking and writing skills among students. Based on these results, it is recommended that teachers implement the IPBL JEMBER model in English instruction to improve students' critical thinking and writing abilities. This approach allows educators to better guide students toward a more active, reflective learning process that encourages critical analysis.